Routing problems for vehicle ad-hoc networks using the virtual message ferry routing scheme. (2018) - Wang, Chu-Fu; Chiu, Yang-Chih
The communication links between vehicles in vehicle ad-hoc networks (VANETs) suffer from the intermittent connection problem due to node mobility, and consequently the routing design is very challenging. The virtual message ferry (VMF) routing scheme is one of the efficient approaches for aiding the routing decisions in VANETs to cope with the routing problem. The role of the VMF can be played by any vehicle on the road, and the current VMF role-playing vehicle will be switched to another vehicle when it drives away from the preplanned VMF trajectory. The considered VMF routing scheme will not alter the driving behaviour of any chosen vehicle, which includes its driving speed, the original relocating plan, etc. This paper considers routing problems in the VMF backbone network that are formed by trajectories of multiple VMFs. A network optimisation problem formulation and transformation are given. Heuristic algorithms to find near optimal solutions are also proposed.